Prospective study evaluating the predictability of need for retreatment with intravitreal ranibizumab for age-related macular degeneration - Juhasz Liebermann, Anne; Suter, Christian; Iglesias, Katia (My University, 2013)
Purpose To investigate the rhythm and predictability of the need for retreatment with intravitreal injections of ranibizumab for neovascular age-related macular degeneration (nAMD).
Methods This prospective study enrolled 39 patients with treatment-naïve nAMD. After three loading doses of intravitreal ranibizumab, patients underwent an intensified follow-up for 12 months (initially weekly, then with stepwise increases to every 2 weeks and to monthly after each injection). Patients were retreated on an as-needed basis if any fluid or increased central retinal thickness (CRT) (>50μm) was found on spectral domain optical coherence tomography (OCT). Statistical analysis included patients who received at least two retreatments (five injections).
Results A mean of 7.5 injections (range 0–12) were given between months 3 and 15. The mean visual acuity increased by 13.1 and 12.6 ETDRS letters at months 12 and 15 respectively. Two or more injection–retreatment intervals were found in 31 patients. The variability of their intra-individual intervals up to 14 weeks was small (SD 0–2.13 weeks), revealing a high regularity of the retreatment rhythm. The SD was correlated with the mean interval duration (r = 0.89, p < 0.001). The first interval was a good predictor of the following intervals (regression coefficient =0.81). One retreatment criterion was stable in 97 % of patients (cysts or subretinal fluid).
Conclusion The results of this study demonstrate a high intra-individual predictability of retreatment need with ranibizumab injections for nAMD. These findings may be helpful for developing individualized treatment plans for maintained suppression of disease activity with a minimum of injections and visits.
Keywords: Neovascular age-related macular degeneration; Ranibizumab; Intravitreal injection; P.R.N. treatment regimen; Predictability; Optical coherence tomography